Conceptual basics for unity in multi ethnic diversity : the Qur'anic and prophetic paradigm - Gilani, Sayyid Muhammad Yunus; Islam, Tazul (University Malaya, 2012)
Islam affirms that the universe is a unity emanating from a single Will of the Sustaining Lord; and man himself is a part of this universe, dependent upon and related to all other parts; individuals are as atoms in the universe, therefore, they must have the same dependence upon and relation to one another. So, the Islamic belief is that the humanity is an essential unity; its scattered elements must be brought together, its diversity must give place to unity. This worldview of unity in diversity or cosmopolitanism is widely seen in the Qur’an and the Prophetic practices of multi-cultural unification which overwhelmingly focus on freedom of religion, inter-religious symbiosis and reciprocal obligations, religious tolerance, just and equal treatment to the non-Muslim subjects and social security towards them, conflict resolution, developing mutual understanding through dialogue and mutual cooperation in common interest. This paper aims to introduce the Islamic concepts of cosmopolitanism in a theoretical and practical framework by conducting an analytic textual reading of the concerned Qur’anic verses and a historical survey of the Prophet’s (pbuh) efforts at unity in diversity